Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/agronomy12092112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Altitude Gradient on the Physiological Performance of Quinoa in the Central Region of Colombia

Abstract: The conditions of the agroecological environment play a fundamental role in the physiological performance of quinoa; however, due to the accelerated expansion of quinoa cultivation and the great diversity of cultivars present in the world, it has not been possible to study the effect that their interaction can have, which brings with it problems in productivity and even in the adaptability of cultivars. The aim of this research was to evaluate the physiological performance of seven quinoa cultivars under three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
4
1
Order By: Relevance
“…There are also numerous studies, with various quinoa cultivars, in which protein contents have been found to be in the medium and low ranges, or even lower than those found in our work, for the Chimborazo ecotype. Thus, in a study conducted in the central region of Colombia, the physiological performance of seven quinoa cultivars was evaluated at three altitude gradients (cold, temperate, and warm climates), and protein values ranged from 12% to 17% [22]. In contrast to our results, these studies observed that the reduction in the altitudinal gradient had a positive association with the protein content in the grain (p < 0.001).…”
Section: Water Activity and Proximate Compositioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There are also numerous studies, with various quinoa cultivars, in which protein contents have been found to be in the medium and low ranges, or even lower than those found in our work, for the Chimborazo ecotype. Thus, in a study conducted in the central region of Colombia, the physiological performance of seven quinoa cultivars was evaluated at three altitude gradients (cold, temperate, and warm climates), and protein values ranged from 12% to 17% [22]. In contrast to our results, these studies observed that the reduction in the altitudinal gradient had a positive association with the protein content in the grain (p < 0.001).…”
Section: Water Activity and Proximate Compositioncontrasting
confidence: 99%
“…The protein content in quinoa grains depends not only on the variety, but also on cultural practices and geographical factors, such as chemical composition of the soil, climate, or water availability [22,23]. These factors can interact in complex ways, making it challenging to identify the exact cause of variations in the protein content of quinoa ecotype Chimborazo.…”
Section: Water Activity and Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 In most cultivars, the endosperm is rich in fats and proteins, components that are stored in the lipid and protein bodies. 8 While, the perisperm contains uniform cells filled with starch granules. 9 These granules are present as individual entities or as spherical aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported the existence of more than 16,000 varieties of quinoa accessions around the world, showing the structural attributes and antioxidant capacities of six quinoa cultivars with high productive potential in the central regions of Colombia (García-Parra et al, 2020, 2021. On the other hand, edaphoclimatic conditions have a differential effect on quinoa cultivars, which can alter quinoa production, modifying the compositional characteristics of its seeds (García-Parra et al, 2022). Consequently, several publications have been made in relation to the physicochemical properties and behavior of the components of quinoa, including the quantification of moisture, lipids, and protein of raw materials for the validation of high protein flour (Muñoz-Pabon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%